Data analytics on electricity consumption - Pan, Jiacong (2018)
Energy Research Institute @ NTU (ERI@N) has been collecting electricity meter readings for several buildings in Nanyang Technological University (NTU). This project aims to carry out data analytics on the electricity consumption in NTU to discover insights and anomalies in the data and replace anomalies in the data by estimates from the normal trend.